2017
DOI: 10.21037/jtd.2017.11.58
|View full text |Cite
|
Sign up to set email alerts
|

Semi-rigid single hook localization the best method for localizing ground glass opacities during video-assisted thoracoscopic surgery: re-aerated swine lung experimental and primary clinical results

Abstract: Background: The aim of this study was to compare the effects of currently available preoperative localization methods, including semi-rigid single hook-wire, double-thorn hook-wire, and microcoil, in localizing the pulmonary nodules, thus to select the best technology to assist video-assisted thoracoscopic surgery (VATS) for small ground glass opacities (GGO).Methods: Preoperative CT-guided localizing techniques including semi-rigid single hook-wire, doublethorn hook-wire and microcoil were used in re-aerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our in vitro experiments proved that the sodium alginate magnetic fluid immediately formed a gel after contact with the curing agent. The maximum magnetic force between the magnetic gel and the pursuit magnet was 0.22 N, which is similar to the maximum anchoring force of the traditional micro-coil method reported in the literature (0.20 N) 38 . The force was sufficient to make a tuberous part protrude from the lung surface without causing the magnetic gel to fall away.…”
Section: Discussionsupporting
confidence: 84%
“…Our in vitro experiments proved that the sodium alginate magnetic fluid immediately formed a gel after contact with the curing agent. The maximum magnetic force between the magnetic gel and the pursuit magnet was 0.22 N, which is similar to the maximum anchoring force of the traditional micro-coil method reported in the literature (0.20 N) 38 . The force was sufficient to make a tuberous part protrude from the lung surface without causing the magnetic gel to fall away.…”
Section: Discussionsupporting
confidence: 84%
“…Ultrasonography offers a quick, affordable, less invasive way of localizing lesions but is limited by the presence of air in the lungs [12]. Based on the mentioned above, we compared the advantages and disadvantages between single semi-rigid hook wire, double-thorn hook wire and micro-coil through a swine lung experiment and found that semi-rigid hook wire showed the better operability than the other two, which was already published in December 2017 [13]. In the present study, 74 consecutive patients with 81 pulmonary nodules underwent CT-guided single semi-rigid hook wire localization prior to VATS were examined.…”
Section: Discussionmentioning
confidence: 99%
“…We previously conducted a localization experiment in the swine lung and reported that among the commonly used three location methods, semi-rigid hook wire showed better operability and practicability than double-thorn hook wire and micro-coil [13]. In the present study, we continued to use the semi-rigid single hook wire localization technique for individuals during VATS resection.…”
Section: Introductionmentioning
confidence: 92%
“… 1 Image-guided hook wires, which are now used in surgery, particularly in spinal surgery, thoracoscopic surgery, and breast surgery, allow for the precise localization of tumor sites. 2 , 3 We report the case of a woman undergoing laparoscopic partial nephrectomy in which a hook wire was used. The hook wire facilitated the localization of the lesion and avoided cutting into the lesion directly.…”
Section: Introductionmentioning
confidence: 99%